Problems Encountered by the Police Officers in Cybercrime Unit in Addressing Cybercrime Cases: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The ideal of the study is to understand the connections between the use of online crimesurveillance methods and former victims, the perception of the frequency of cybercrime, andthe perception of its impact. This study aims to probe perspectives on cybercrime,victimization gests, and the operation of online crime forestallment ways. It increases people'sdependency on the Internet, which is a nest for malicious activity such as cybercriminals.The results are presented in the sequence of the problem raised in Chapter 1 and containtabular data analysis and textual interpretation to further describe the results gathered.Specifically, the study will answer the following research questions. The profile of therespondents, problems encountered by the police officers in the cybercrime unit in addressingcybercrime cases, how the respondents assess the problem encountered by Police Officers inaddressing in cybercrime unit, measures and inputs that may be utilized to address theproblems Encountered by Police Officers in Cybercrime Unit, and Finding may be utilized theProblems Encountered by Police Officers in Cybercrime Unit in Cybercrime Cases.
Keywords: Criminology